Steven Pinker : estruturas mentais inatas e a ontologização do homo oeconomicus - Pin, Leonardo Michelangelo Veloso [UNIFESP] (2016)
The theme of human nature is of central importance in discussions about society, because it guides the way in which individuals see themselves, as well as what would be the nature of their relationship with others. Make part of this topic the question of innate and acquired, that is, what would be universal and immutable in the human beings and what would be the result of socialization by means of interpersonal relationships in which they are located. The Canadian author Steven Pinker says that the human mind model that he divulges, based on evolutionary psychology that is based, for its turn, on a type of biological determinism, would solve the problem of innate and acquired at the same time that would fight what he calls the Standard Social Science Model as the model for the analisys of the relationship between individual and society. However, the Pinker´s model about the human mind and society seems to be based on the ontologization of a theoretical model called Homo eoconomicus present in the so-called methodological individualism. The objective of this project is analyzing whether the criticism that Pinker weaves to what he calls the Standard Model of Social Sciences has strong fundamentals and if the model of human being presented by its evolutionary psychology would be not only a hypostatization of a simple theoretical construct with heuristic objectives: the methodological individualism.